The elements of news construction model in Malaysia - Siti Suriani Othman; Liana Mat Nayan; Lee, Kuok Tiung (2014)
What becomes news in one country is different from another, and this is connected with the fact that news construction is a complex process. When discussing the complexity of news construction, one of the most important criteria that should not be neglected is the specificity of news construction in a certain country and/or culture. As such, the news construction model in Malaysia is one of the examples of a complex and specific process, as Malaysia is an Islamic country home to a multi-ethnic and multi-religious society. Thus, this paper will discuss two concepts that are suggested as the foundations of the news construction model in Malaysia. They include the principles of Islam and its connection to journalism practice, and multiculturalism. In discussing this, the paper argues that, these concepts are unable to demonstrate complexity and specificity of news construction in Malaysia, but they enable further the focus on the specificity of Malaysian news to be explored and extended by future studies.